Mobile Robot navigation modelling, control and applications - De Melo, Leonimer Flávio; Alves, Silas Franco dos Reis [UNESP]; Rosário, João Maurício (My University, 2012)
This work presents and discusses the main topics involved on the design of a mobile robot system and focus on the control and navigation systems for autonomous mobile robots. Introduces the main aspects of the Robot design, which is a holistic vision about all the steps of the development process of an autonomous mobile robot; discusses the problems addressed to the conceptualization of the mobile robot physical structure and its relation to the world. Presents the dynamic and control analysis for navigation robots with kinematic and dynamic model and, for final, presents applications for a robotic platform of Automation, Simulation, Control and Supervision of Mobile Robots Navigation, with studies of dynamic and kinematic modelling, control algorithms, mechanisms for mapping and localization, trajectory planning and the platform simulator. © 2012 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Embedded Control Architectures; Mobile Robots Dynamic and Kinematic Modelling and Simulation; Mobile Robots Navigation